1991
DOI: 10.1177/088532829100500403
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane-Covered Mammary Prosthesis: A Nine Year Follow-Up Assessment

Abstract: We have examined ten tissue capsules from patients ranging from five months to nine years of mammary implantation. Contrary to published reports of polyurethane foam "fragmentation" or "disappearance" in the capsules evaluated, the polyurethane foam was still present and embedded in the surrounding tissue capsule. The foam was nearly always invisible by gross observation, or manual palpation. Only after enzymatic digestion of the tissue capsule did the foam become clearly visible as continuous sheets. ESCA ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Different implant surfaces may increase or decrease the risk of CC. Several studies described a low incidence of CC with PU implants, a benefit that does not decrease over time [9,31,33,49,50]. After formation of the capsule around the implant, the PU foam breaks down to become an integral part of the capsule, and it is proven that this observed tighten tissue adhesion does not occur with textured silicone implants [17,24,28,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Different implant surfaces may increase or decrease the risk of CC. Several studies described a low incidence of CC with PU implants, a benefit that does not decrease over time [9,31,33,49,50]. After formation of the capsule around the implant, the PU foam breaks down to become an integral part of the capsule, and it is proven that this observed tighten tissue adhesion does not occur with textured silicone implants [17,24,28,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, early investigations reported that the polyurethane foam biodegrades rapidly after implantation 45, 46. However, subsequent analyses suggested that polyurethane foam implants biodegrades through a slow process47 and that large amounts of unbroken polyurethane foam still remains 9 years after implantation 48. Therefore, we believe further assessments on the rate of biodegradation of polyurethane among augmented women are needed to clarify our findings.…”
Section: Discussionmentioning
confidence: 68%